Kipidap: A mobile app designed for Malaysian university students to overcome procrastination - Husni, Sharifah Shafiqa Syed; Kamaruzaman, Muhamad Fairus; Wahyuni, Novi Sri (Humanities, Arts and Social Sciences Studies, 2025)
Currently students at the Malaysian Institute of Technology (UiTM) Malaysia are having trouble getting their work done on time. This affects their health and grades. The Kipidap application created for android users was designed using the Pomodoro Technique, allowing users to accomplish tasks straight away rather than postponing them. Finding out how frequently UiTM students put off activities and assessing the results were the key objectives. The respondents were 100 UITM students. They were equally divided between men and women and comprised a broad spectrum across academic disciplines, particularly in regard to work completion speed and time management skills, the data revealed notable variations. There are useful tools in the Kipidap mobile app that assist with managing oneself and working more efficiently. These include an intelligent task management system, a Pomodoro timer for effective work sessions, and inspiring incentives such discount coupons to keep people interested. Of the participants, 98% stated they utilized the educational content on the mobile app, 95% said they loved how easy it was to use, and 97% said it was simple enough to navigate their way around. Kipidap is a handy, simple, and efficient tool for students who want to improve their performance in the classroom and create positive habits that will benefit.